Compartmentalized Structure of the Moderator Band Provides a Unique Substrate for Macroreentrant Ventricular Tachycardia. (August 2018) - Walton, Richard D.; Pashaei, Ali; Martinez, Marine E.; Constantin, Marion; Duchateau, Josselin; Bear, Laura; Cros, Caroline; Pascarel-Auclerc, Caroline; Guo, Yunbo; Benoist, David; Dubes, Virginie; Faye, Ndeye Rokhaya; et al.
Abstract : Background: Papillary muscles are an important source of ventricular tachycardia (VT). Yet little is known about the role of the right ventricular (RV) endocavity structure, the moderator band (MB). The aim of this study was to determine the characteristics of the MB that may predispose to arrhythmia substrates. Methods: Ventricular wedge preparations with intact MBs were studied from humans (n=2) and sheep (n=15; 40–50 kg). RV endocardium was optically mapped, and electrical recordings were measured along the MB and septum. S1S2 pacing of the RV free wall, MB, or combined S1-RV S2-MB sites were assessed. Human (n=2) and sheep (n=4) MB tissue constituents were assessed histologically. Results: The MB structure was remarkably organized as 2 excitable, yet uncoupled compartments of myocardium and Purkinje. In humans, action potential duration heterogeneity between MB and RV myocardium was found (324.6±12.0 versus 364.0±8.4 ms; P <0.0001). S1S2-MB pacing induced unidirectional propagation via MB myocardium, permitting sustained macroreentrant VT. In sheep, the incidence of VT for RV, MB, and S1-RV S2-MB pacing was 1.3%, 5.1%, and 10.3%. Severing the MB led to VT termination, confirming a primary arrhythmic role. Inducible preparations had shorter action potential duration in the MB than RV (259.3±45.2 versus 300.7±38.5 ms; P <0.05), whereas noninducible preparations showed no difference (312.0±30.3 versus 310.0±24.6 ms, respectively). Conclusions: The MB presents anatomic and electrical compartmentalization between myocardium and Purkinje fibers, providing a substrate for macroreentry. The vulnerability to sustain VT via this mechanism is dependent on MB structure and action potential duration gradients between the RV free wall and MB. Abstract : Supplemental Digital Content is available in the text.